An Analysis of Traumatic and Non-Traumatic Hemopericardium Using Autopsy Data From a County Medical Examiner. Issue 8 (August 2022) - Klutts, Garrett; Kalkwarf, Kyle; Meyer, David; Yang, Yijiong; Wolf, Dwayne A.; Bhavaraju, Avi; Margolick, Joseph; Marino, Katy; Robertson, Ron; Drake, Stacy A.
The volume of hemopericardium requiring hemodynamic changes in the trauma patient is not well understood. We performed a study using autopsy data from trauma patients who died with hemopericardium (>20 mL). Of 1848 traumatic deaths, 54 had hemopericardium at autopsy. The median pericardial blood in this group was 150 mL, which is more than the previously assumed volume to be lethal in trauma patients. Therefore, it may be appropriate to redefine the estimated volume required to cause lethal hemopericardium in trauma patients.